Focus on the dabrafenib, vemurafenib, and trametinib in clinical outcome of melanoma: a systematic review and meta-analysis - Ida Ayu Widya Anjani; Anak Agung Bagus Putra Indrakusuma; I Gede Krisna Arim Sadeva; Putri Ayu Wulandari; Luh Made Mas Rusyati; Prima Sanjiwani Saraswati Sudarsa; I Gede Putu Supadmanaba; Desak Made Wihandani (Bali Dermatology and Venereology Journal, 2020)
Background: Melanoma is the most serious lethal skin cancer, affects the melanin producer cells (melanocytes). Surgery is the most common treatment, whereas for the advance stage the development of a treatment is recommended. BRAF (Dabrafenib and Vemurafenib) inhibitor or MEK inhibitor (Trametinib) is used as the most frequently targeted therapy of melanoma due to more than 80% patient with positive BRAF mutation. In this review, those treatments will be investigated systematically to identify their clinical outcome.Method: This systematic literature review (SLR) was performed from Cochrane, Science Direct, Google Scholar, and Pubmed. Cochrane Risk-of-Bias Tool RoB2 is used to assess RCT studies and New-castle Ottawa Scale Assessment to assess cohort studies by 3 different assessors. Data analysis was carried out by using Review Manager (RevMan 5.4). Heterogenicity test was assessed by I2 Â and Chi2 statisticResult: There are 20 studies used in this article (13 RCT and 7 cohorts). The overall survival (OS) and progression-free survival (PFS) of study that using targeted therapy (vemurafenib, trametinib, or dabrafenib) compare other therapies (chemotherapy, immunotherapy,etc) showed risk ratio (RR) was 1.12 (95%CI 1.07,1.17;Â  I2=100%; p<0,00001). The OS and PFS with monotherapy compare of vemurafenib, trametinib, or dabrafenib with combination therapy showed RR was 1.09 (95%CI.06,1.13;I2=99%; p<0,00001). Conclusion: BRAF and MEK targeted therapy has a good prognosis for a patient with a positive BRAF gene mutation and could be combined with other therapy for a better clinical outcome rather than monotherapy.Keyword: melanoma, dabrafenib, vemurafenib, and trametinib